The Effects of Education on Vietnamese Youth’s Purposes of Life - Quy Thanh, Nguyen; Hung, Le Thai; Thuy, Tang Thi; Anh, Tran Lan; Anh, Nguyen Thuy; Ha, Le Thi Hoang; Lien, Vu Phuong; Bich, Nguyen Thi (VNU Journal of Science: Education Research, 2020)
The main objective of this research was to analyze the relationship between eduation levels of Vietnamse Youth and their puposes of life. We used the data from the School-to-Work Transition Survey-SWTS in 2012-2015. Both descriptive statistics and multinomial logit regression analyses were used for the study. We provide the first evidence that higher levels of education is closely linked with having purpose of non-monetary life purposes, namely contributing to society; a successful career or a happy family. In addtion, such effects tend to increase with higher levels of education. Thus, our research finding implies that better education not only offers economic benefits for educated individuals but also for their family, communities and society.